THE EFFECT OF PROFITABILITY AND CORPORATE GOVERNANCE ON TAX AVOIDANCE (Empirical Study on Mining Companies and Basic Industry and Chemical Companies Listed on the Indonesia Stock Exchange for the period 2016 - 2020) - Ineu Dewi Santika; Indah Umiyati; Sri Mulyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
The purpose of this study is to examine the effect of profitability and corporate governance on tax avoidance. Corporate governance in this study is measured by proxy independent commissioners, audit quality, and managerial ownership. This study uses a population of Mining Companies and Basic Industry and Chemical Companies Listed on the Indonesia Stock Exchange for the period 2016 - 2020. The method of determining the sample used is purposive sampling. Hypothesis testing used in this study used panel data regression analysis. The results of this study indicate that the variables of profitability and managerial ownership have a significant positive effect on tax avoidance, while the independent commissioner and audit quality variables have no significant effect on tax avoidance.